2011
DOI: 10.1007/s11250-011-9826-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of conventional and extended intra-mammary treatment of persistent sub-clinical mastitis with cefquinome in lactating dairy cows

Abstract: The objectives of the present study were to evaluate the efficacy of intra-mammary-administered cefquinome for the treatment of sub-clinical mastitis in lactating dairy cows and to determine if extended therapy would enhance treatment efficacy. Seventy-three Holstein dairy cows from a single farm with 150 infected quarters were enrolled in the study. Infected cows were allocated randomly to one of three treatment regimens: (1) conventional (standard) regimen: 75 mg of cefquinome administered three times at 16-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
6
0
2
Order By: Relevance
“…It is important to note that because we did not have an untreated control group in the study reported here we cannot claim that IMM cefquinome was an efficacious treatment for experimentally induced S. aureus mastitis in goats. Efficacy is supported by the results of studies in dairy cows, demonstrating that IMM cefquinome is efficacious when infused in cows with coliform mastitis (Shpigel et al, 1997), Streptococcus uberis mastitis (Milne et al, 2005), caused by coagulase-negative staphylococci, environmental streptococci, and coliforms (Kasravi et al, 2011), S. aureus mastitis (Swinkels, Cox, Schukken, & Lam, 2013), and a number of mastitis pathogens (Bradley & Green, 2009).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is important to note that because we did not have an untreated control group in the study reported here we cannot claim that IMM cefquinome was an efficacious treatment for experimentally induced S. aureus mastitis in goats. Efficacy is supported by the results of studies in dairy cows, demonstrating that IMM cefquinome is efficacious when infused in cows with coliform mastitis (Shpigel et al, 1997), Streptococcus uberis mastitis (Milne et al, 2005), caused by coagulase-negative staphylococci, environmental streptococci, and coliforms (Kasravi et al, 2011), S. aureus mastitis (Swinkels, Cox, Schukken, & Lam, 2013), and a number of mastitis pathogens (Bradley & Green, 2009).…”
Section: Discussionmentioning
confidence: 95%
“…aureus mastitis in goats. Efficacy is supported by the results of studies in dairy cows, demonstrating that IMM cefquinome is efficacious when infused in cows with coliform mastitis (Shpigel et al, ), Streptococcus uberis mastitis (Milne et al, ), caused by coagulase‐negative staphylococci, environmental streptococci, and coliforms (Kasravi et al, ), S . aureus mastitis (Swinkels, Cox, Schukken, & Lam, ), and a number of mastitis pathogens (Bradley & Green, ).…”
Section: Discussionmentioning
confidence: 96%
“…Mastitis is one of the representative diseases in dairy cows and remains the most costly disease. It reduces milk yield and affects the quality of the milk in all dairy-producing countries in the world [1]. It is estimated that between 2 and 55% of all lactating cows will include a mastitis infection [2].…”
Section: Introductionmentioning
confidence: 99%
“…(Perry & Schentag, 2001). Cefquinome (CFQ), a fourth-generation cephalosporin, is effective against clinically important bacteria such as Streptococcus spp., Staphylococcus spp., Enterobacteriaceae, Pasteurellaceae, and gram-positive anaerobes (Amiridis, Fthenakis, Dafopoulos, Papanikolaou, & Mavrogianni, 2003;Kasravi et al, 2011;Limbert et al, 1991;Orden, Ruiz-Santa-Quiteria, García, Cid, & De La Fuente, 1999). CFQ has been recommended for the treatment of septicemia caused by E. coli in neonatal calves at 2 mg/kg dose, given once daily (CVMP, 1995;Thomas et al, 2004).…”
mentioning
confidence: 99%